2022
DOI: 10.1002/sce.21781
|View full text |Cite
|
Sign up to set email alerts
|

Science faculty conceptions of equity and their association to teaching practices

Abstract: Equity in education has been conceptualized in various ways, which provides different affordances and constraints for policy, research, and teaching decisions. Regarding the latter, there is a dearth of research on how postsecondary science faculty conceptualize equity and whether and how their understandings of equity may be informing their teaching and related practices. This study examined equity conceptions and reported teaching practices among 45 faculty members in a College of Sciences at a research inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…For example, while two of the classes with the TR condition had a heavier emphasis on high-stakes exams in the overall grade, three had nearly the same grading scheme as the classes with the CT condition, although as noted earlier, exams in the classes with the TR condition had a higher emphasis on mathematics (vs conceptual) than the classes with the CT curriculum. Use of the CT curriculum, with attendant heavier basis of the overall grade on course components other than high-stakes exams, has been shown to be associated with reduced race and gender gaps for students at a Hispanic-serving R1 university, 74,94 and this study now adds evidence that when using this curriculum, likely with higher conceptual-to-mathematics emphasis on high-stakes exams that accompanies the CT curriculum, an asset-based supplemental intervention closes these gaps at a Third, students who enrolled in the asset-based intervention when they were in GC1 (Group 1) had lower GC2 outcomes than their peers who were invited and did not enroll (Group 2) as well as their peers who were not invited (Group 3) (Figure 4). Furthermore, students who were invited but did not enroll (Group 2) in the intervention during GC1 did not differ statistically in GC2 outcomes from students who were not invited (Group 3).…”
Section: ■ Discussion and Implicationsmentioning
confidence: 99%
“…For example, while two of the classes with the TR condition had a heavier emphasis on high-stakes exams in the overall grade, three had nearly the same grading scheme as the classes with the CT condition, although as noted earlier, exams in the classes with the TR condition had a higher emphasis on mathematics (vs conceptual) than the classes with the CT curriculum. Use of the CT curriculum, with attendant heavier basis of the overall grade on course components other than high-stakes exams, has been shown to be associated with reduced race and gender gaps for students at a Hispanic-serving R1 university, 74,94 and this study now adds evidence that when using this curriculum, likely with higher conceptual-to-mathematics emphasis on high-stakes exams that accompanies the CT curriculum, an asset-based supplemental intervention closes these gaps at a Third, students who enrolled in the asset-based intervention when they were in GC1 (Group 1) had lower GC2 outcomes than their peers who were invited and did not enroll (Group 2) as well as their peers who were not invited (Group 3) (Figure 4). Furthermore, students who were invited but did not enroll (Group 2) in the intervention during GC1 did not differ statistically in GC2 outcomes from students who were not invited (Group 3).…”
Section: ■ Discussion and Implicationsmentioning
confidence: 99%
“…For example, in the context of COVID‐19, Edward used scientific numeracies to advance an argument about combating racism and hate crimes. While several scholars have identified pervasive racism in science education structures (e.g., Cheuk, 2021; Russo‐Tait, 2023), made cogent calls to take up racism in the science classroom (e.g., Sheth, 2019), and shown how racism can serve as a foundational point of inquiry within innovative and justice‐oriented science curricula (e.g., Donovan et al, 2019; Morales‐Doyle, 2017), we still see racism as a topic addressed only infrequently in most science classrooms. We suspect that such infrequency stems from many sources, including—but certainly not limited to—widespread perception of inquiry around racism as not fulfilling current standards, given that it does not explicitly appear as a target idea (e.g., NGSS Lead States, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Studies such as Rodriguez et al (2012) have demonstrated how different framings of equity can result in different interpretations, influencing the research questions and the results that are found. Similarly, because teachers' beliefs and conceptions of equity impact their views of their roles in education and shape their practice (Buehl and Beck, 2015;Cochran-Smith et al, 2016;Russo-Tait, 2022), it is important to explicitly articulating one's equity definition while doing equity work. Regardless of its significance, teachers' various understanding of equity is still unclear in literature (See Bartell and Meyer, 2008;Jackson and Jong, 2017 for a few examples).…”
Section: Introductionmentioning
confidence: 99%